Aspects of the biology and population structure of Oreochromis niloticus, Coptodon zillii and Oreochromis leucostictus tilapia in Lake Naivasha, Kenya. Issue 1 (3rd March 2022) - Yongo, Edwine; Agembe, Simon W.; Manyala, Julius O.; Waithaka, Edna
Abstract: The Nile tilapia ( Oreochromis niloticus ), Redbelly tilapia ( Coptodon zillii ) and Blue spotted tilapia ( Oreochromis leucostictus ) were introduced into Lake Naivasha in the 1950s to diversify and boost the lake fisheries. These species have since been exploited in the commercial gillnet fishery. The fish stocks, however, are currently facing problems of pollution, wetland degradation and intense fishing pressures. Accordingly, the present study investigated some aspects of the biology and population structure of the three tilapiine species in light of changing lake conditions. Fish samples were collected from January to December 2019 using multifilament gillnets of 2.0‐to‐6.0‐inch mesh sizes. Immediately after their capture, the fish specimens were transported to the lab for morphometric measurements and analysis of maturity. The highest and lowest mean (±SD) total length (TL) were exhibited by O .  niloticus (22.9 ± 5.2 cm) and C .  zillii (14.5 ± 2.1 cm), respectively. Similarly, O .  niloticus exhibited a higher mean weight (268.4 ± 18.0 g) and body depth (7.6 ± 2.5 cm), compared to the other species. O .  niloticus exhibited an isometric growth pattern, while C .  zillii and O .  leucostictus exhibited negative allometric growth. The fish species were in good condition, with mean condition factors of 1.59 ± 0.07, 1.51 ± 0.06 and 1.23 ± 0.03 for C .  zillii, O .  leucostictus and O .  niloticus, respectively. Furthermore, the condition factors for O .  leucostictus and O .  niloticus varied by size class, exhibiting a decreasing trend with increased fish size. The male:female sex ratio revealed significantly more males than females for O .  niloticus (2.30:1.0) and O .  leucostictus (2.36:1.0), although not for C .  zillii (1.15:1.0). O .  niloticus (28.0–29.0 cm TL) matured at a larger size, followed by O .  leucostictus (21.0–26.0 cm TL), and C .  zillii (15.0–17.0 cm TL). In comparison, values of length‐weight parameters, condition factor, sex ratio and size at first maturity of the studied fishes varied in Lake Naivasha, Victoria, Albert and George. The gillnet mesh ≤3.0″ mainly targeted small‐sized immature fish, while mesh ≥4″ targeted mature fish, particularly O .  niloticus . It was concluded that gillnets with ≥4.0″ mesh could safely be applied for this fishery in Lake Naivasha, whereas the use of smaller mesh should be controlled to protect the juveniles as a means of maintaining sustainable fisheries. Furthermore, the present study also provided useful information, including size at maturity that is vital for setting mesh size for managing the lake fishery.